"This is capitalism. It is not illegal": Users' attitudes toward institutional privacy following the Cambridge Analytica scandal. Issue 2 (31st December 2020) - Afriat, Hagar; Dvir-Gvirsman, Shira; Tsuriel, Keren; Ivan, Lidor
Abstract: In this study, we seek to understand the considerations of young adults who chose to continue their active engagement with Facebook even after Cambridge Analytica scandal laid bare the mechanics of economic surveillance. We base our analysis on two sets of in-depth face-to-face interviews we conducted with young adults in Israel—26 before the Cambridge Analytica scandal, which we had already conducted for a study on privacy, and 24 after the scandal erupted. To analyze our respondent's rationales, we employ Boltanski and Thévenot's regimes of justification framework. Before the scandal, our respondents largely saw privacy as a commodity, a tradeoff made by the individual—information disclosure in exchange for free personalized digital services. However, there were some respondents who rejected the notion of privacy as a commodity and advanced an alternative perspective that considers it to be a human right. After the Cambridge Analytica scandal, there was a marked shift away from understanding of privacy as a right, which our respondents neither saw an unconditional right nor something enforceable by regulators. Instead, they largely saw economic surveillance as something inherent to the digital world, which one needs to accept if one wants to participate in it.